2019
DOI: 10.12968/bjon.2019.28.17.s24
|View full text |Cite
|
Sign up to set email alerts
|

Nursing considerations for supporting cancer patients with metastatic spinal cord compression: a literature review

Abstract: Background: metastatic spinal cord compression (MSCC) is an oncology emergency. Prevalence is increasing. Treatment and care are complex and those diagnosed may be faced with life-changing challenges. Aims: to review the impact and management of MSCC in patients with cancer, in order to analyse nursing considerations for supporting patients. Methods: a literature review and thematic analysis of five primary research papers, published between 2009 and 2014. Findings: two themes of prognosis/survival time and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…. These findings were in agreement with Al Attar W.2015 (58 ) who report that the majority (55%) of nurses in study group are within the age of (31)(32)(33)(34)(35)(36)(37)(38)(39)(40), and also supported by Won Kim H and et al 2019 ( 59) who reported that Majority (57.2 %) of respondents belonged to the age group of (26-35) years.…”
Section: Table (2) Showed Percent Distribution Of Levels and Mean Sco...supporting
confidence: 92%
See 1 more Smart Citation
“…. These findings were in agreement with Al Attar W.2015 (58 ) who report that the majority (55%) of nurses in study group are within the age of (31)(32)(33)(34)(35)(36)(37)(38)(39)(40), and also supported by Won Kim H and et al 2019 ( 59) who reported that Majority (57.2 %) of respondents belonged to the age group of (26-35) years.…”
Section: Table (2) Showed Percent Distribution Of Levels and Mean Sco...supporting
confidence: 92%
“…Nursing assessment usually consists of two main domains, taking the patients health history and physical examination. The history of the symptoms and disease process will help determine if the patient is experiencing autonomic dysfunction (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) .…”
Section: Introductionmentioning
confidence: 99%
“…Family caregivers face numerous dimensions of care burden, including their physical, psychological, and social health [ 11 ]. Many studies have researched family caregivers’ experiences and the need to support care at home in different country contexts [ 12 , 13 ]. There are personal care challenges related to the cultures and beliefs of family caregivers of persons with metastases cancer, which affect the caring role and the health status of family caregivers and their ability to meet patient needs [ 14 ].…”
Section: Introductionmentioning
confidence: 99%